Versioning of IFC-based information models for collaborative design - Jaly Zada, Aras Jalal (2016)
The engineering design process is an iterative and distributed process. It is often characterized by multi-disciplinary teams in multiple places working together, on a single project, using different models and software tools. The current collaboration approaches in AEC industry often focus on integrating and managing multiple models from multi-designers. Building Information Modelling (BIM) is playing a major role in facilitating collaboration. BIM provides an opportunity to electronically model and manage the vast amount of information embedded in a building project, from conception to completion. In the design process, changes in the models are inevitable and very common. They can occur at any stage of the project, from different sources, and for various reasons, which can have significant effects on the process. Versioning is a solution for design change management. Many model versions can be created and distributed among the disciplinary teams. Despite many researches done on the subject and the availability of some software applications that deal with changes in design, the mechanism to cope with the changes among different model versions needs further studies to increase the management efficiencies and ensure designers have an up-to-date version of the model. The challenges of information exchange in project management result from: a combination of the enormous amounts of information generated, the large variety of design systems involved, and data format utilised by different disciplines at various design stages. The Industry Foundation Classes (IFC) standard represents a paradigm shift for data and information exchange. The main goal for developing the IFC model is to provide a neutral data format to exchange information among different software programs. IFC models reflect the current state of BIM model. They do not take into consideration the process and results of latest changes among different BIM users nor record the history of earlier changes. This research work therefore investigates how to improve the process of managing the design changes from different disciplinary models. This research developed a collaborative methodology to manage the design changes in different models. It tackles the challenges of the versioning process as a change management approach. This is done through extending the capability of the existing IFC schema to control and manage different design changes in different BIM models. The proposed extended IFC incorporates the changed information of the latest model version and provides the complete history of changes of all earlier model versions. A prototype system was developed in this research to implement and validate the extended IFC and to demonstrate using it to improve the management of the whole design process. The research process involved undertaking a literature review to identify knowledge gaps and challenges in the areas of the (design process, BIM, IFC, and change management). The research also investigated and analysed the IFC standard and identified two key requirements of extending the IFC and implementing the prototype. Further aspects of this research include developing a framework to facilitate a collaborative design, extending the existing IFC schema, designing and implementing the prototype based on the extension, and validating and evaluating the extended IFC and the prototype system. The research concludes that the extended IFC to handle versioning can effectively improve collaborative design. It addressed concepts involving comparing, storing, classifying, extending managing, versioning, exchanging, and sharing of modelling information in a collaborative way. The proposed process of managing design changes covered an important gap associated with current IFC models, which can be incorporated in future releases of the IFC standard.